Efficient Small‐Molecule Organic Solar Cells by Modulating Fluorine Substitution Position of Donor Material. Issue 7 (21st February 2023) - Zhang, Tao; Lv, Qianglong; Peng, Zhongxiang; An, Cunbin; Bi, Pengqing; Xu, Ye; Yang, Ni; Wang, Jingwen; Xian, Kaihu; Ye, Long; Zhang, Shaoqing; Hou, Jianhui
Comprehensive Summary: The fluorine substitution position in organic semiconductors is critical in improving device performance for organic solar cells (OSCs). Herein, two similar small‐molecule donors, B3T‐P o F and B3T‐P m F, are designed and synthesized, which only differ on the fluorine substitution position on the pendent benzene unit. Although both small‐molecule donors exhibit similar absorption profiles and molecular energy levels, B3T‐P m F has stronger crystallinity and lower energetic disorder than B3T‐P o F. After blending with the non‐fullerene acceptor of BO‐4Cl, B3T‐P m F shows better phase separation and more ordered molecular packing in blend film. As a result, the B3T‐P o F:BO‐4Cl‐based OSC shows a power conversion efficiency (PCE) of 12.3%. In contrast, the B3T‐P m F:BO‐4Cl‐based cell demonstrates obviously increased J SC and FF values, thus yielding an excellent PCE of 14.7%. This study indicates that reasonable selection of fluorine atom substitution position in conjugated side chains is one of the promising strategies for achieving high‐performance SM‐OSCs. Abstract : Two small‐molecule donors with different fluorine substitute positions were synthesized, and their photovoltaic properties were studied.